"Keeping You in the Know": The Effect of an Online Nursing Journal Club on Evidence-Based Knowledge Among Rural Registered Nurses. Issue 4 (April 2019) - DuGan, Joyce E.
Abstract : The purpose of this research study was to promote and evaluate clinical scholarship in rural registered nurses through the dissemination of evidence-based practice findings via the development and implementation of an online nursing journal club. A simple pretest-posttest design was selected to implement this project. Along with descriptive data, survey data were analyzed using a paired t test. A convenience sample from a rural university nursing alumni email database spanning 2010–2011 and 2014–2016 was invited to participate. Three articles, one each month, were presented on the journal club Web site. Along with the 10-question pretest and posttest, the Evidence-Based Practice Questionnaire survey was completed after the third article posttest. By the end of the third month, 37 participants completed all three articles and Evidence-Based Practice Questionnaire survey. The results of the paired t tests all revealed a significant mean difference increase in knowledge from pretest to posttest ( P < .05). In addition, the Evidence-Based Practice Questionnaire survey revealed that participants felt "good" about their knowledge of evidence-based practice related to areas such as reviewing practice skills, ability to identify gaps in practice, ability to analyze critical evidence, ability to determine how valid material is, and ability to apply information to individual cases.